Soil moisture conservation in water-deficit hill agriculture: Affordable to small landholdings - Choudhury, Burhan U (Indian Farming, 2023)
Rain-fed agriculture in the hills of north-eastern India is at the risk of crop failure, primarily due to over-dependence on inconsistent distribution and variable intensity of rainfall. Intermittent long dry spell between monsoon months (June–September) delay the timely planting of summer crops. In the rainless (